2007
DOI: 10.1021/bi0620860
|View full text |Cite
|
Sign up to set email alerts
|

Pre-steady-State Currents in Neutral Amino Acid Transporters Induced by Photolysis of a New Caged Alanine Derivative

Abstract: Na + -dependent transmembrane transport of the small neutral amino acids, such as glutamine and alanine, is mediated, among others, by the neutral amino acid transporters of the solute carrier 1 (SLC1, ASCT1 and 2) and SLC38 families (SNAT1, 2 and 4). Many mechanistic aspects of amino acid transport by these systems are not well understood. Here, we describe a new photolabile alanine derivative, based on protection of alanine with the 4-methoxy-7-nitroindolinyl (MNI) caging group, which we use for pre-steady-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…5 B in the presence of intracellular K + , a cation that is not thought to interact with ASCT2. Rapid alanine application through photolysis of caged alanine (Zhang et al, 2007) within less than a microsecond (Fig. 5 A; released [alanine], ∼600 µM) resulted in a small transient inward current that rapidly relaxed back to a steady state within ∼10 ms (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 B in the presence of intracellular K + , a cation that is not thought to interact with ASCT2. Rapid alanine application through photolysis of caged alanine (Zhang et al, 2007) within less than a microsecond (Fig. 5 A; released [alanine], ∼600 µM) resulted in a small transient inward current that rapidly relaxed back to a steady state within ∼10 ms (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Control experiments with nontransfected cells demonstrate the absence of current signals upon application of the laser flash. Further control experiments are shown in Zhang et al (2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrogenic Na ϩ binding appears to be a hallmark of many Na ϩ -driven, secondary active transporters and has been also demonstrated for glucose transporters (9), GABA transporters of the SLC6 family (10), amino acid transporters (11), and phosphate transporters (12).…”
mentioning
confidence: 95%
“…and glycine 4, 4 L-aspartate 5, 5 and L-alanine 6, 6 which have been applied in various biological systems. Detailed pharmacological evaluation has found that caged glutamates 1 and 2 do not bind to glutamergic receptors prior to photolysis and are therefore suitable reagents for investigations of synaptic transmission.…”
Section: Introductionmentioning
confidence: 99%